Los 90 años de Estudios Eclesiásticos - de Diego, Rafael María Sanz (Estudios eclesiásticos, 2012)
This article reconstructs the history of the review Estudios Eclesiásticos from his birth in 1922. With this aim, the author divides his 90 years of life in three stages: the first periode spreads from his foundation until 1942; the second phase comes up to the Council Vatican II (1962); the third periode studies the last five decades of the review until the present. For each one of these phases the author evokes the most relevant events in the history of the Church in Spain and in the world. This study is from great usefulness to know the whole production of the magazine in the diverse theological disciplines.